Intrinsic and extrinsic motivation is associated with computer-based auditory training uptake, engagement, and adherence for people with hearing loss - Henshaw, Helen; McCormack, Abby; Ferguson, Melanie A. (Frontiers in Psychology, 2015)
Hearing aid intervention typically occurs after significant delay, or not at all, resulting in an unmet need for many people with hearing loss. Computer-based auditory training (CBAT) may provide generalized benefits to real-world listening, particularly in adverse listening conditions, and can be conveniently delivered in the home environment. Yet as with any intervention, adherence to CBAT is critical to its success. The main aim of this investigation was to explore motivations for uptake, engagement and adherence with home-delivered CBAT in a randomized controlled trial of adults with mild sensorineural hearing loss (SNHL), with a view to informing future CBAT development. A secondary aim examined perceived benefits of CBAT. Participants (n = 44, 50-74 year olds with mild SNHL who did not have hearing aids) completed a four-week program of phoneme discrimination CBAT at home. Participants’ experiences of CBAT were captured using a post-training questionnaire (n = 44) and two focus groups (n = 5 per group). A mixed-methods approach examined participants’ experiences with the intervention, the usability and desirability of the CBAT software, and participants’ motivations for CBAT uptake, engagement and adherence. Self-Determination Theory was used as a theoretical framework for the interpretation of results. Participants found the CBAT intervention easy to use, interesting and enjoyable. Initial participation in the study was associated with extrinsic motivation (e.g. hearing difficulties). Engagement and adherence with CBAT was influenced by intrinsic (e.g. a desire to achieve higher scores), and extrinsic (e.g. to help others with hearing loss) motivations. Perceived post-training benefits included better concentration and attention leading to improved listening. CBAT also prompted further help-seeking behaviors for some individuals. We see this as an important first-step for informing future theory-driven development of effective CBAT interventions.